Distressed situation and renegotiation plan: a case study - Bonoldi, Aurelio Vittorio (2014)
This work presents a real case of a company in a distressed situation: PlywoodCo. The objective of this work is to understand why PlywoodCo. got in its current distressed situation and, based on that, propose a financial renegotiation plan compatible to that situation in order to turn PlywoodCo. into a viable company. An introduction is made, in order to put the reader in touch with PlywoodCo., presenting its activities, main products, market position as well as briefly introducing the company’s current situation. Following the introduction, the literature review is displayed, describing the theory related to and applied in this work. Later, the methodology is presented, followed by further information on PlywoodCo.’s operations and financials, highlighting the company’s relationship with stakeholders, operational indexes, financial statements, debt schedule and depreciation schedule. Than the assumptions, analysis and projections are presented, consisting of two parts: (1) a diagnose section addressing PlywoodCo.’s current situation; and (2) a projections section, which will be divided in two further micro parts: (a) PlywoodCo.’s financial projections in the current debt schedule it is in; and finally (b) the financial situation of PlywoodCo. under the new proposed plan. Finally, it is concluded that PlywoodCo. will need further efforts besides the debt renegotiation in order to overcome its distress situation. After renegotiating the debt, the company will need R$ 23 MM until the end of 2013.